Enhanced formation quality and tensile shear load of 7B04 aluminum alloys lap joint by impacting flow friction stir lap welding - Zhang, Zhiqing; Liu, Hua; Ji, Shude; Zhang, Jiaqi; Jin, Chen; Ma, Lin; Song, Qi (Journal of materials research and technology, 2024)
Avoiding the upward-bending hook is a highly pressing and challenging task in the field of similar aluminum alloys friction stir lap welding (FSLW). To enhance formation quality and then obtain the welded lap joint with high tensile shear load, a novel impacting flow FSLW (IF-FSLW) process based on the X-shape reverse-threaded pin was proposed in this study. Three welding tools with different tool geometry parameters were developed to analyze how the locations of the materials accumulated zone (MAZ) influenced the joint formation and the joint loading capacity, and 7B04 aluminum alloys were chosen as research subject. Results showed that the horizontally-impacting and vertically-impacting effects of MAZ on and above the original lap interface made the hook respectively present the forky structure at the end and the downward-bending morphology, and the horizontally-impacting effect of MAZ made the stir zone (SZ) have a protruding morphology near the MAZ. Under the tensile fracture mode, the IF-FSLW joint under configuration A had a greatly heightened tensile shear load under the combined actions of the downward-bending hook and the enlarged SZ. The tensile shear load of IF-FSLW joint reached 8.62 kN/mm under the reasonable combination of tool geometry parameters and welding process parameters. The IF-FSLW process by the X-shape reverse-threaded pin provides an effective way to obtain a superb-strength lap joint of aluminum alloys.